2017
DOI: 10.1302/2046-3758.61.bjr-2016-0142.r1
|View full text |Cite
|
Sign up to set email alerts
|

Metal-backedversusall-polyethylene unicompartmental knee arthroplasty

Abstract: ObjectivesUp to 40% of unicompartmental knee arthroplasty (UKA) revisions are performed for unexplained pain which may be caused by elevated proximal tibial bone strain. This study investigates the effect of tibial component metal backing and polyethylene thickness on bone strain in a cemented fixed-bearing medial UKA using a finite element model (FEM) validated experimentally by digital image correlation (DIC) and acoustic emission (AE).Materials and MethodsA total of ten composite tibias implanted with all-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…Concerns have thus been raised regarding the incidence of tibial loosening/subsidence in all-polyethylene tibial components [ 4 , 24 ], and the role of implant stiffness in unexplained pain [ 12 , 19 , 25 ]. Such variable survival rates from 56% at 7 years (32–75 95% CI) [ 4 ] to 87.6% at 10 years [ 9 ] in all-polyethylene designs suggest that not all all-polyethylene designs are equal, and this may reflect component thickness [ 13 ]. Components of 6 mm thickness have been significantly associated with early clinical failure [ 26 ], increased wear and osteolysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns have thus been raised regarding the incidence of tibial loosening/subsidence in all-polyethylene tibial components [ 4 , 24 ], and the role of implant stiffness in unexplained pain [ 12 , 19 , 25 ]. Such variable survival rates from 56% at 7 years (32–75 95% CI) [ 4 ] to 87.6% at 10 years [ 9 ] in all-polyethylene designs suggest that not all all-polyethylene designs are equal, and this may reflect component thickness [ 13 ]. Components of 6 mm thickness have been significantly associated with early clinical failure [ 26 ], increased wear and osteolysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological cancellous bone overload and tibial subsidence may affect thinner implants more so than thicker implants. Finite element analysis has shown that increasing all-polyethylene thickness to 10 mm still under-performs in terms of proximal tibial strain compared to metal-backed implants [ 13 ] with the added cost of increased tibial resection and associated reduction in cancellous bone strength [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FE modelling has being increasingly used for implant biomechanical optimization, 17 , 18 custom-implant development, 19 , 20 and tissue engineering. 21 We have previously developed an FE model of a healthy 7.9-year-old male hip from CT data.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, excessive interference increases the assembly load required to implant the component which in turn generates stress in the bone, trabecular damage and increases the risk of fractures. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%